APLIKASI PENGOLAHAN DATA KURSUS BAHASA INGGRIS MEI CABANG SIMPANG RIMBO KOTA JAMBI - Mulyadi - (JURNAL AKADEMIKA)
The author formulates the problem in this penelitiaan problem as follows : " What sort of data processing applications English language courses MAY branch intersection Rimbo using visual basic 6.0 " In this study, the objectives of the authors of this article are : Trying to overcome obstacles or problems encountered in data processing English language courses intersection branch May Rimbo and Designing a new application system that is more effective in the data penggolahan melakukaan English language courses intersection branch May Rimbo pemerograman this by using visual Basic 6.0 . The end of the implementation of this research can be authors conclude : With the development of the new system is expected to help the data processing English language courses in May were fast and efficient , data processing English language courses intersection branch May Rimbo still use manual and miscrofot office excel 2003 and computerized system used to create and process data in May English language courses Rimbo branch intersections using visual Basic 6.0 program